2016
DOI: 10.1159/000453362
|View full text |Cite
|
Sign up to set email alerts
|

Dronedarone Modulates M<sub>1</sub> and M<sub>3</sub> Muscarinic Receptors with Subtype Selectivity, Functional Selectivity, and Probe Dependence

Abstract: We have previously reported that amiodarone interacts with a novel allosteric site on muscarinic receptors. Amiodarone's most striking effect is to enhance the maximal response elicited by muscarinic agonists at the M1, M3, and M5 receptors. Furthermore, the quaternary analog N-ethylamiodarone (NEA) is inhibitory at these receptors and appears to compete with amiodarone at that allosteric site. In the present studies, we show that dronedarone also modulates Gq-mediated response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(65 reference statements)
3
6
0
Order By: Relevance
“…Given the importance of HRV on a whole series of parameters and variables, it has been shown how antiarrhythmic agents alter HRV with a direct effect on the ANS and myocardial contractility. Different comparative analyses showed that Amiodarone, despite interacting with the ANS centrally [ 49 ] and peripherally [ 50 , 51 ] did not affect HRV. On the other hand, Flecainide and Propafenone have vagolytic [ 52 ] and beta-blocking [ 53 ] properties, which could further modulate sympathetic and parasympathetic activity in the heart [ 54 , 55 ] decreasing all the parameters of HRV in the time domain and the frequency domain including the markers of vagal activity [ 56 ].…”
Section: Emotional Dysegulation and Heart Rate Variabilitymentioning
confidence: 99%
“…Given the importance of HRV on a whole series of parameters and variables, it has been shown how antiarrhythmic agents alter HRV with a direct effect on the ANS and myocardial contractility. Different comparative analyses showed that Amiodarone, despite interacting with the ANS centrally [ 49 ] and peripherally [ 50 , 51 ] did not affect HRV. On the other hand, Flecainide and Propafenone have vagolytic [ 52 ] and beta-blocking [ 53 ] properties, which could further modulate sympathetic and parasympathetic activity in the heart [ 54 , 55 ] decreasing all the parameters of HRV in the time domain and the frequency domain including the markers of vagal activity [ 56 ].…”
Section: Emotional Dysegulation and Heart Rate Variabilitymentioning
confidence: 99%
“…Amiodarone is best known as an antiarrhythmic agent that blocks potassium channels, but it has also been shown to enhance muscarinic receptor activity through an allosteric mechanism. [24][25][26] Initial studies con rmed that amiodarone is a PAM of ACh at M 1 receptors, based on measurements of [ 3 H]-AA release in stably transfected CHO cells (Fig. 2; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“… 24 A similar phenomenon has been observed at the M 1 and M 5 muscarinic subtypes. 25 , 26 We are not aware of any other PAM of a G protein-coupled receptor that increases the maximal response of the endogenous ligand without enhancing its potency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows a therapeutic efficacy for treating Alzheimer's disease, Huntington's disease, and schizophrenia in the animal model (192)(193). Amiodarone Gq-mediated responses are positively modulated at M 1 mAChR and M 3 mAChR but inhibited in a more discriminating fashion at the M 1 mAChR (194,195).…”
Section: 8-dihydroxyflavone (78-dhf)mentioning
confidence: 99%